PRE-DISPUTE OF LAND WAKAF IN THE PERSPECTIVE OF ARTICLE 40 OF LAW NO. 41 OF 2004 ON WAKAF AS A SOLUTION TO EDUCATIONAL ISSUES IN INDONESIA - Syarif Hidayatullah; Ahmad Sarmadi (Yasi Learning Education Research, 2025)
This is study examines the pre-dispute of land waqf in the perspective of Article 40 of Law No. 41 of 2004 as a solution to education problems in Indonesia, with a focus on the community in Tangerang. The complex issue of secondary education raises tensions between the legal meaning and practice of waqf, especially related to the use of waqf assets for education. The research method used was qualitative with data collection through interviews, observations, and documentation at the Al Mabrurotul Munawwaroh Al Amanah Foundation. Interviews were conducted with education managers, related officials, and administrators of the Indonesian Waqf Board (BWI). The results of the study show that the prevention of waqf disputes is highly dependent on transparent and participatory asset management, as well as the understanding of rights and obligations through socialization. The ambiguity of the waqf pledge deed needs to be overcome to strengthen the legitimacy of management. The conflict between the heirs and the nadzir reflects a social dynamic that requires a constructive solution. These findings confirm that a clear legal framework and collaboration between parties are essential to utilize land waqf in improving access and quality of education in Indonesia.